Bibliometric analysis of global research in palliative care for cervical cancer - Almobarak, Fhaied (Frontiers in Oncology, 2024)
Objective: The present study aims to conduct a comprehensive bibliometric analysis of global research in palliative care for cervical cancer, providing insights into publication trends, authorship patterns, influential journals, and thematic concentrations.Methods: A bibliometric analysis approach was employed using metadata extracted from Scopus spanning 2000-2023. The search utilized main terms related to cervical cancer and palliative care. Data analysis and visualization were performed using the Bibliometrix R Package's web app Biblioshiny and VOSviewer software.The study identified 2,492 publications on palliative care for cervical cancer, with a notable peak in 2021. The analysis revealed a diverse publication landscape, encompassing primarily articles. Citation analysis showed a staggering 63,994 citations. The most relevant journals were The Lancet Oncology, Gynecologic Oncology, and International Journal of Gynecological Cancer. The study also highlighted influential authors, institutions, and countries, with Harvard University,